PERTUMBUHAN EKONOMI, INVESTASI ASING LANGSUNG DAN EMISI KARBON DI INDONESIA PERIODE 1990-2022: Economic Growth, Foreign Direct Investment, and Carbon Emission in Indonesia During 1990-2022 - Arifah, Lidyana (Elastisitas : Jurnal Ekonomi Pembangunan, 2023)
Climate change caused by the increasing of carbon emission needs to get serious attention from the society and the policy maker. One of the key factors that makes the carbon emission advance almost uncontrollably is the economic activities such as industrial action. This paper examines the relationship between economic growth, investment, and carbon emissions in Indonesia over the period 1990-2022. Time series data are used to investigate this correlation. The result indicate there is a positive relationship between GNI and carbon emissions, which confirm the environmental Kuznets Curve. As for the Foreign Direct Investment, the result indicate that estimated coefficient is negative.